2017
DOI: 10.1590/0037-8682-0455-2016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of amphotericin B deoxycholate versus N-methylglucamine antimoniate in pediatric visceral leishmaniasis: an open-label, randomized, and controlled pilot trial in Brazil

Abstract: Introduction: Despite their high toxicity, antimonials and amphotericin B deoxycholate are commonly used for treating visceral leishmaniasis (VL). Few studies showing conflictive data about their efficacy and adverse events in pediatric population are available. This study aimed to evaluate efficacy and safety of amphotericin B deoxycholate vs. that of N-methylglucamine antimoniate in treating pediatric VL in Brazil. Methods: This was a randomized, open-label, 2-arm and controlled pilot clinical trial. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…The choice of MA as the reference arm was based on the prevailing Brazilian VL treatment guidelines at the time when the study was started in 2011 [5], as well as data obtained from a clinical trial that had been concluded in 2009 [13]. AmphoB and LAMB regimens were included as these were routinely used in Brazil and had been included in 2011 into the new treatment guidelines to reduce the VL fatality rate [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of MA as the reference arm was based on the prevailing Brazilian VL treatment guidelines at the time when the study was started in 2011 [5], as well as data obtained from a clinical trial that had been concluded in 2009 [13]. AmphoB and LAMB regimens were included as these were routinely used in Brazil and had been included in 2011 into the new treatment guidelines to reduce the VL fatality rate [14].…”
Section: Methodsmentioning
confidence: 99%
“…AmphoB and LAMB regimens were included as these were routinely used in Brazil and had been included in 2011 into the new treatment guidelines to reduce the VL fatality rate [14]. The same regimen of AmphoB had also been used in the above-referenced clinical trial conducted in 2009 [13]. The selection of the combination therapy with LAMB single dose plus MA was based on the lack of local efficacy evidence for miltefosine and PM, and the satisfactory efficacy rates reported for MA, the first line treatment in the country.…”
Section: Methodsmentioning
confidence: 99%
“…Published cases of fatal toxicity related to antimonials include severe toxic hepatitis and pancreatitis 7 , fatal arrhythmia 23 , and unexpected sudden death 20 . In pediatric patients, a recent trial showed that N-methylglucamine antimoniate (n = 51) and amphotericin B deoxycholate (n = 50) had similar cure rates (94.1% vs. 94%, respectively) and serious adverse events (SAE) incidence was similar in both groups 24 . Treatment may be complicated with drug interactions between antileishmanial and other administered medications and their coinciding toxicity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Obtained by the sum of the product of the multiplication of the cost of the meglumine antimoniate vial (US$ 1.30) by the number of vials per day [2] by the number of days of treatment [10], and the product of the multiplication of the cost of the liposomal amphotericin B vial (US$ 18.76) by the number of vials per day [8] by the number of days [1]. 11 Obtained by multiplying the average daily cost of hospitalisation (US$ 16.03) and the average duration of treatment (10.33 days). 12 Obtained by multiplying the daily wage loss (US$ 10.68) by the time of 25.33 days of absence from work (10.33 days of hospitalisation plus 15 days of home recovery).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Incidentally, the therapeutic arm evaluating AMBD in the study by Romero et al (2017) was suspended following the recommendation of the data safety monitoring board due to safety issues [10]. Also, the evidence on efficacy and safety of AMDB in Brazil is restricted to one clinical trial comparing AMBD with MA in children aged 6 months to 12 years [11]. Thus, the purpose of this study was to estimate the cost-effectiveness of strategies for the treatment of VL in Brazil to aid decision-making in the public health system.…”
Section: Introductionmentioning
confidence: 99%